Unlocking the potential of indigenous Saccharomyces cerevisiae from Maraština grapes for use as starter cultures in the winemaking process - Ana Boban; Vesna Milanović; Federica Cardinali; Sanja Radman; Andrea Osimani; Lucia Aquilanti; Cristiana Garofalo; Giorgia Rampanti; Irena Budić-Leto (Applied Food Research)
The emerging trend in winemaking highlights the importance of microbiological terroir, emphasising the use of indigenous Saccharomyces cerevisiae strains as starter cultures. In this study, 117 indigenous S. cerevisiae yeasts were isolated for the first time from spontaneously fermented Maraština musts collected from vineyards within three subregions of the Dalmatian winegrowing region (Croatia). The isolates were identified at a molecular level and evaluated for oenological traits. Compared to isolates from other regions, those from Central and Southern Dalmatia (CSD) exhibited high tolerance to sulfur dioxide (up to 250 mg/L) and osmotic stress (up to 50% glucose), low hydrogen sulphide and acetic acid production, and occasional protease activity. In contrast, isolates from Northern Dalmatia (ND) exhibited higher ethanol tolerance (up to 14%) but lower enzymatic activity and moderate sulfur dioxide resistance. The 11 best-performing isolates selected for further evaluation were glucophilic and completed fermentation within 15 days. The isolates from CSD produced higher ethanol concentrations (up to 12.59%) than those from other regions. Wines fermented with indigenous strains showed reduced total acidity and malic acid concentrations compared to those fermented with commercial yeast EC 1118. Isolates from CSD, in particular, significantly enhanced the aromatic complexity of the wines, primarily through increased ester production, whereas isolates Z-1, O-2, and V-7 from ND vineyards excelled in producing higher alcohols. These findings demonstrate the regional identity of indigenous S. cerevisiae strains and their potential to enhance wine typicity. This study links native yeast biodiversity with subregional traits, supporting their use in terroir-driven winemaking.